UJI STABILITAS POOLED SERA YANG DISIMPAN DALAM FREEZER UNTUK PEMANTAPAN MUTU INTERNAL DI LABORATORIUM KLINIK - Anik Handayati; Juliana Christyaningsih; Tjipto Rini (JURNAL PENELITIAN KESEHATAN, 2014)
Stability of control sera is very important in order to assess the performance of a laboratory, including quality instruments and reagents. Some small laboratories are using pooled sera as a control sera for day-to- day examination. In general, the temperature of the freezer is used to save serum in - 7 to - 4the freezer is frequently opened  and closed so it is likely the temperature is too unstable. This study was an experiment laboratory, with  the time series control group design. The serum was analyzed the influence of storage time in the freezer at a temperature of -7 to -4ºC and a temperature of – 15stability of the normal and abnormal of pooled sera and examination were using the parameters of glucose, cholesterol and uric acid in serum. Samples were divided into 9 groups: 0,  1, 2 , 3 , 4 , 5, 6, 7 , 8 weeks. Data were analyzed with regression equations. The storage effect on normal and abnormal of blood glucose level in the freezer temperature -7 º to -4 º C for 8 weeks but at - 15temperature had no effect on both normal and abnormal of serum glucose level. There was no effect of storage in a freezer temperature -7 º to -4 º C and -15 º C for 8 weeks on cholesterol levels and normal and abnormal uric acid. Key Word: stability, control of sera, freezer, internal quality, clinical laboratory